Frequency and Etiology of Maxillofacial Fractures in Tertiary Care Hospital - Khadim Shah, Hidayatullah, Zahid Qayyum, Saifullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Trauma is a global issue that causes illness and death. Maxillofacial fractures are common following trauma. Aims: To determine the frequency and etiology of maxillofacial fractures in oral and maxillofacial trauma patients. Study Design: Descriptive cross-sectional. Methodology: The entire study population was adult having oral and maxillofacial trauma visiting the outpatient/emergency department at Hayatabad Medical Complex, Peshawar from April to October 2018. Patients (n=205) were enrolled. Detailed history with examination was done. An OPG (orthopantomogram) radiographic confirmation of maxillofacial fracture was performed, PA face (Reverse Towne’s view open mouth), occipitomental (OM) view, sub-mentovertex (SMV) view and computerized tomography (CT) scan when needed. All this information was recorded on Performa. Statistical analysis: Data was analyzed using SPSS version 26. Results were presented as frequency and percentage. Results: Majority of patients (56.1%) suffered from road traffic accidents, 3.4% patients had few of them (3.4%) had sports injuries, 11.7% patients had interpersonal violence or firearm injuries while rest (18.1%) had injures from animals. As per maxillofacial surgeries, 3.9% patients had maxilla fractures, 10.7% patients had mandible fractures, 17.8% patients had zygomatic complex fractures, 13.2% naso-orbital fractures, 13.2% orbit fractures, 16.6% had frontal bone fractures, and 34.6% had nasal bone fractures. Conclusion: The study concluded that the most common supporting maxillofacial trauma is young men with a common etiological condition of road accidents.